Application of Learned Optimism and Mindful Parenting for Caregivers of Putra Utama 03 Ceger Orphanage - Yohana Ratrin Hestyanti; Penny Handayani; Abriyanti Riyanti; Sylvidire Maharani; Nelson Zelig; Alyssa Abidin; Tjong Michaella; Stephanie Anggun (Journal of Innovation and Community Engagement, 2021)
There used to be a gap between ideal and actual condition in the pattern of parenting at Panti Sosial Asuhan Anak (PSAA) Putra Utama 03 Ceger, an orphanage. The gap was caused by some factors namely the environment facilities, high levels of problematic behavior among adolescents, the system, insufficient number of caregivers, and cultural factors of parenting that have been going on for a long time in the orphanage. The gap could lead to learned helplessness of the caregivers in parenting pattern on children at the orphanage. A team was formed to create an intervention through community service activity to overcome the problem, by applying learned optimism and mindful parenting for the caregivers at the orphanage. This intervention program was aimed to increase the caregiver’s knowledge and motivation through training of learned optimism and mindful parenting. Therefore, the caregivers can be more optimistic and wholehearted in carrying out their role as caregivers. The approach used in this intervention is based on the Bioecological Model Theory from Bronfenbrenner, the Experiential Learning from Bandura, and the Change Theory by Lewin. The steps taken in this intervention program were a preliminary study using a problem tree, Fishbone Analysis, and SWOT analysis. After a preliminary study, the team prepared an intervention design consisting of preparation, training, monitoring, and evaluation of the intervention. The expected targets of this intervention program were an increasing knowledge in learned optimism training and caregivers’ motivation in applying the training materials. These indicators have been achieved well through the activities provided. Keywords: learned helplessness; learned optimism; mindful parenting; orphanage